Personal Selling sebagai Sarana Promosi Produk Label (Studi Kasus kegiatan Personal Selling pada Divisi Pemasaran PT. National Label Umas Daya) - Handayanti, Asih (Media Nusantara, 2021)
This study discusses the “Personal Selling as a means of product promotion label. The purpose of this study wanted to know Personal selling activities, the use of social media in marketing the product label, and the need to study the behavior of consumers Sales Representative to support the activities of Personal Selling. The theory used is the theory of Marketing, Personal Selling and Theory of Symbolic Interaction. This research was conducted at PT. National Label Umas Daya and as a key informant was four sales representatives who work as personal selling. Researchers used the case study method with qualitative approach and data collection techniques are in-depth interviews, direct observation, and documentation. The results of the study, in doing marketing, sales representatives have done the stages of personal selling as a promotional tool in marketing the product label as expected. The use of internet and social media to support marketing activities.